2011
DOI: 10.1080/10550887.2011.554779
|View full text |Cite
|
Sign up to set email alerts
|

Dual Diagnosis and Chronology of Illness in Treatment-Seeking Italian Patients Dependent on Heroin

Abstract: Although there are studies describing the prevalence of patients with drug addiction and dual diagnosis, there is a paucity of data regarding the progression from psychiatric disorders to drug addiction or vice versa. A total of 1,090 patients dependent on heroin were interviewed to examine the presence of dual diagnosis and the progression from psychiatric disorders to drug dependence or vice versa. A total of 574 patients met the criteria for a dual diagnosis. A total of 362 patients progressed from substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 81 publications
2
17
1
10
Order By: Relevance
“…However, a high prevalence of psychiatric comorbidities, especially depressive, anxiety, and personality disorders, in OD population, is well established (Haro et al, 2004;Roncero et al, 2012;Strain et al, 2002;Wu et al, 2013). The presence of previous mental disorders has been shown to be a predictor of incident substance use/dependence (Katz et al, 2013;Maremmani et al, 2011a;Reidy et al, 2014). However, substance use may also be cause of inducing psychiatric disorders, such as stimulant-or drug-induced psychoses and substanceinduced mood disorders, as well as substance-induced anxiety conditions (Maremmani et al, 2011a;Schuckit, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…However, a high prevalence of psychiatric comorbidities, especially depressive, anxiety, and personality disorders, in OD population, is well established (Haro et al, 2004;Roncero et al, 2012;Strain et al, 2002;Wu et al, 2013). The presence of previous mental disorders has been shown to be a predictor of incident substance use/dependence (Katz et al, 2013;Maremmani et al, 2011a;Reidy et al, 2014). However, substance use may also be cause of inducing psychiatric disorders, such as stimulant-or drug-induced psychoses and substanceinduced mood disorders, as well as substance-induced anxiety conditions (Maremmani et al, 2011a;Schuckit, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…El resultado del presente trabajo es coherente con que la adicción a heroína se ha considerado de mayor gravedad, debido a la problemática social, familiar y a las enfermedades médicas (sobre todo infecciosas) y psiquiátricas a las que se asocia (Maremmani et al, 2011;Sánchez-Hervás et al, 2010). Maremmani y cols.…”
Section: Discussionunclassified
“…This misusing attitude perhaps was partially justified by the fact that the diagnosis of chronic intoxication from substances was often limited to the period of active use, possibly extended over a following trail of socalled prolonged withdrawal. The follow-up of drug addicts and alcoholics through the decades, and between relapses has shed brighter light on the issue of persistent psychiatric damage after detoxification, and suggested that the drug-induced syndromes may outlive the endurance of drug-using habits, following an autonomous course such as spontaneous syndromes would do [2] .…”
Section: Editorialmentioning
confidence: 99%